Cognitive and linguistic effects of narrative-based language intervention in children with Developmental Language Disorder. (May 2021) - Pauls, Laura J; Archibald, Lisa MD
Background and aims: Narrative-based language intervention provides a naturalistic context for targeting overall story structure and specific syntactic goals in children with Developmental Language Disorder (DLD). Given the cognitive demands of narratives, narrative-based language intervention also has the potential to positively impact related abilities such as working memory and academic skills. Methods: Ten children (8–11 years old) with DLD completed 15 sessions of narrative-based language intervention. Results: Results of single subject data revealed gains in language for five participants, four of whom improved on a probe tapping working memory. An additional four participants improved on a working memory probe only. On standardized measures, clinically significant gains were noted for one additional participant on a language measure and one additional participant on a visuospatial working memory. Carry over to reading was noted for three participants and to math for one participant. Across measures, gains in both verbal and visuospatial working memory were common. A responder analysis revealed that improvement in language may be associated with higher verbal short-term memory and receptive language at baseline. Those with working memory impairments were among those showing the fewest improvements across measures. Conclusions: Narrative-based language intervention impacted verbal skills in different ways across individual children with DLD. Implications: Further research is needed to gain an understanding of who benefits most from narrative-based language intervention.